Memahami radikalisme digital: Ancaman dan penaggulangannya - Zuhroh, Alfiyatuz (Maliki Interdisciplinary Journal, 2023)
Digital radicalism is an ideology that seeks digital change or renewal through violent, violent and extreme means. The threat of radicalism to the millennial generation is influenced by various factors such as social media, technology, education and social values. The threat of digital radicalism can be summarized in two ways, namely the internet and mass media. Media control cannot completely stop the virus of radicalism due to current technological limitations. Radical content in digital media may be used as a reference in articles that do not seem radical. Therefore, digital media users must focus on the human factor. The radicalization process occurs in three stages, namely: (1) sensitive stage, (2) group membership, and (3) action stage. Even though Indonesia is basically a moderate Muslim country and it is difficult to develop radicalism in this country, this still happens. That doesn’t mean Indonesia can’t develop this, especially as a destination for the younger generation.